2018
DOI: 10.1016/j.aap.2017.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Burden of injury of serious road injuries in six EU countries

Abstract: The analyses presented in this paper can support further improvement of road safety policy. Countermeasures could for example be focused at reducing skull and brain injuries, spinal cord injuries and injuries to the lower extremities, as these injuries are responsible for more than 90% of the total burden of injury of MAIS3+ casualties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
3
17
1
Order By: Relevance
“…The comparison with other studies on patterns of trauma was limited by the differences in population samples, methods of data collection, number of hospitals involved in the analyses and timeframes taken into account. However, the review of recent literature [10][11][12][13][14][15][16] provided interesting elements of analysis. The incidence of injuries following road traffic collisions has been increasing globally in the last two decades [10], with the exception of countries with high socio-demographic index (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison with other studies on patterns of trauma was limited by the differences in population samples, methods of data collection, number of hospitals involved in the analyses and timeframes taken into account. However, the review of recent literature [10][11][12][13][14][15][16] provided interesting elements of analysis. The incidence of injuries following road traffic collisions has been increasing globally in the last two decades [10], with the exception of countries with high socio-demographic index (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent literature review ( 16 ), self-reported prevalence of disability resulting from road traffic injuries varies between 11% and 80%. Data from the ESPARR cohort study shows that about 75% of the MAIS3+ road traffic casualties have not fully recovered 3 years after the crash ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, road traffic injuries lead to psychological disorders like Post Traumatic Stress Disorder (PTSD) and fear, which in their turn also affect human functioning. Literature reports a prevalence of PTSD between 2% and 33% 1 year postcrash ( 19 ). Moreover, the problems related to human functioning can also lead to socioeconomic consequences like financial or relational problems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations